2022
DOI: 10.3390/rs14153542
|View full text |Cite
|
Sign up to set email alerts
|

A High-Precision Elastic Reverse-Time Migration for Complex Geologic Structure Imaging in Applied Geophysics

Abstract: High-precision elastic reverse-time migration (ERTM) imaging has always been one of the trends in the development of geophysics. However, current wavefield simulations using time-domain finite-difference (FD) approaches in ERTM have second-order temporal accuracy, resulting in travel time changes and waveform distortion in wavefield propagation with large time steps, i.e., temporal dispersion. Errors caused by the temporal dispersion can lead to erroneous imaging locations and out-of-focus diffraction events. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 57 publications
0
1
0
Order By: Relevance
“…Seismic numerical simulation is a crucial research method in seismology, providing valuable insights into the mechanism of earthquakes, seismic event prediction, risk assessment, exploration of the Earth's internal structure, oil and gas exploration, and resource development. Additionally, seismic modeling forms the foundation for full-waveform inversion [1][2][3][4][5][6][7] and reverse-time migration [8][9][10][11][12][13][14], and aids seismic interpretation.…”
Section: Introductionmentioning
confidence: 99%
“…Seismic numerical simulation is a crucial research method in seismology, providing valuable insights into the mechanism of earthquakes, seismic event prediction, risk assessment, exploration of the Earth's internal structure, oil and gas exploration, and resource development. Additionally, seismic modeling forms the foundation for full-waveform inversion [1][2][3][4][5][6][7] and reverse-time migration [8][9][10][11][12][13][14], and aids seismic interpretation.…”
Section: Introductionmentioning
confidence: 99%
“…In order to circumvent such difficulties, modern ultrasonic testing techniques often involve full acoustic or elastic wave-equation modeling. In this paper, we address the 3D ultrasonic imaging of a pipeline using the reverse-time migration (RTM) technique, which has received much attention in the field of geophysics [35][36][37][38][39]. In recent years, RTM methods, originating from seismic imaging, have gained popularity in ultrasonic nondestructive testing applications [40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%
“…Though full-waveform inversion using SGFD with the highorder accuracy in time has been proposed (Fang et al, 2020;Ren et al, 2021), 3D ERTM with a temporal high-order SGFD method has not been reported. We take our previous numerical simulation and migration imaging work (Chen et al, 2016b;Fang et al, 2022a) a step further toward the 3D ERTM workflow, improving parts such as source and receiver wavefield simulation, wavefield reconstruction, and MPI parallelism using GPUs (Fang et al, 2022b). We develop a high-accuracy 3D ERTM workflow based on a P/S decoupled quasi-stress-velocity elastic equation, solved by using the SGFD method with high-order accuracy in time and space.…”
Section: Introductionmentioning
confidence: 99%